ETIKA KOMUNIKASI DALAM PENGASUHAN SANTRI PERSPEKTIF AL-QUR’AN SURAT LUQMĀN AYAT 12-19 (Studi di Pondok Pesantren Al-Husna Deli Serdang) - Yasirul Amri (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2017)
ABSTRACTThis study aims to analyze the application of communication ethics in parenting perspective santri Qur'an letter Luqmān verses 12-19. This research was conducted at Pondok Pesantren Al-Husna Deli Serdang and focused on the care of students only. This research is a qualitative research through phenomenology approach. Methods of data collection is done by interview, observation and documentation, while data analysis method is done by reducing, displaying and verify data. The results showed that 3 of 5 ethic communicators namely the value of confidence and confident the truth of the message content, the value of patience, and the value of affection on the communicant is well implemented while 2 others are exemplary and decency has not been applied by the whole teachers. Then 2 ethics for the communicant ethics of attentiveness and selective attitude has not shown the maximum application by students seen from the results of teaching and learning activities. As for the 3 values of message ethics, Al-Husna boarding school has paid great attention to the first ethics of priority, diction and intonation demonstrated by disciplinary guidance, teaching practice activities for students and evaluation by leaders for teachers in weekly meetings. Furthermore, it is also known that the supporting factors for the implementation of ethics in nurturing are: the role of leadership, dormitory system, adequate facilities and infrastructure, while the inhibiting factors are: quality and quantity of human resources, environmental influences, partial parental role, and cost issues.